A study on the association of body mass index and anthropometry, blood, seminal, and hormonal profile of infertile and fertile males: baseline data - Mamparampil Sasidharan Pillai, Vaishnavi; Kembeeram, Palani; Sinaiah Surulimuthu, Muthiah; Narendiran , Jothi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Globally, people are drastically changing lifestyle behaviors include, unhealthy eating habit, physically inactive and poor sleep quality leads to accumulation of fat in the body including abdomen leads to obesity and it is one of the major risk factors for non-communicable diseases (NCDs) including male infertility. Methods: This randomized control trail conducted in 80 male participants, were divided into four groups include non-obese infertile, obese infertile, non-obese fertile and obese fertile based on the body mass index (BMI) and semen parameters. The anthropometry, blood, seminal and hormonal and lifestyle parameters was analyzed. Association of BMI with the study parameter was analyzed by Pearson’s correlation. Results: Correlation analysis between BMI and anthropometry parameters include age (r=0.14), body weight (r=0.85), waist circumference (r=0.81), systolic blood pressure (BP) (r=0.14) and diastolic BP (r=0.16) shows positive association. Similarly, blood parameters include fasting blood sugar (FBS) (r=0.44), postprandial blood sugar (PPBS) (r=0.33), glycated haemoglobin (HbA1c) (r=0.45), cholesterol (r=0.28), triglycerides (r=0.32) show positive correlation and in contrast high density lipoprotein (HDL) (r=-0.02) shows negative association. Pearson correlation analysis shows that BMI with seminal parameters include volume (r=-0.25), count (r=-0.34), motility (r=-0.38) shows negative correlation. Similarly, hormonal parameters include follicle stimulating hormone (FSH) (r=-0.07), luteinizing hormone (LH) (r=-0.20), testosterone (r=-0.33) and vitamin D (r=-0.16) shows negative correlation. It was observed that unhealthy lifestyle and stress can also mainly cause for higher BMI leads to poor semen quality and hormonal imbalance. Conclusions: The results of present study concluded that BMI is one major risk factor that directly influence the anthropometry, blood, seminal and hormonal parameters. Thus, BMI can be used as the potential marker to assess the tested variables in the study.